It’s Not the Facebook Access, but the Partisan Bias which Predict Belief in Misinformation: The Case of 2019 Indonesia Presidential Election - Halida, Rizka (UI Scholars Hub, 2020)
This study aims to understand the role of Facebook access and partisan bias on the belief in misinformation in the political context of the 2019 Presidential Election. Frequent use of Facebook and partisan bias for presidential candidates were predicted to influence belief in misinformation about illegal migrant workers from China in Indonesia. Using a structured questionnaire, a total of 1,818 participants who were representative of the Indonesian voter population were interviewed using a structured questionnaire asking about their frequency of Facebook use, political support, awareness, and belief in misinformation about thousands of illegal migrant workers from China, as well as other demographic variables as part of national survey questions. Of these, there were 804 participants who were aware of misinformation about illegal migrant workers from China to be analyzed. The results of binomial logistic regression analysis showed that partisan bias significantly affected belief in misinformation —Subianto's (vs Widodo's) supporters significantly have (vs. have not) a belief in the misinformation, whereas the frequency of Facebook usage and the effect of their interactions were not significant. This finding shows the strength of the influence of political support on belief in misinformation and the need to further study the influence of social media in Indonesia's political context.